The pan-cancer lncRNA MILIP links c-Myc to p53 repression - Yu Chen Feng; Xiao Hong Zhao; Liu Teng; Rick F. Thorne; Lei Jin; Xu Dong Zhang (Molecular & Cellular Oncology, 2021)
We have recently identified the MYC proto-oncogene, bHLH transcription factor (MYC, best known as c-Myc)-responsive pan-cancer lncRNA c-Myc-Inducible Long noncoding RNA Inactivating P53 (MILIP) as an oncogenic driver. Our studies show that MILIP facilitates tumor protein p53 (TP53, best known as p53) turnover by reducing its SUMOylation through suppressing tripartite-motif family-like 2 (TRIML2), thus promoting cell survival, proliferation, and tumorigenicity. MILIP may thus represent an anti-cancer target for counteracting the c-Myc axis.